Oxcarbazepine-loaded polymeric nanoparticles: development and permeability studies across in vitro models of the blood–brain barrier and human placental trophoblast - Lopalco, Antonio (Int J Nanomedicine, 2015)
Encapsulation of antiepileptic drugs (AEDs) into nanoparticles may offer promise for treating pregnant women with epilepsy by improving brain delivery and limiting the transplacental permeability of AEDs to avoid fetal exposure and its consequent undesirable adverse effects. Oxcarbazepine-loaded nanoparticles were prepared by a modified solvent displacement method from biocompatible polymers (poly(lactic-co-glycolic acid) [PLGA] with or without surfactant and PEGylated PLGA [Resomer(®) RGPd5055]). The physical properties of the developed nanoparticles were determined with subsequent evaluation of their permeability across in vitro models of the blood–brain barrier (hCMEC/D3 cells) and human placental trophoblast cells (BeWo b30 cells). Oxcarbazepine-loaded nanoparticles with encapsulation efficiency above 69% were prepared with sizes ranging from 140–170 nm, polydispersity indices below 0.3, and zeta potential values below -34 mV. Differential scanning calorimetry and X-ray diffraction studies confirmed the amorphous state of the nanoencapsulated drug. The apparent permeability (P(e)) values of the free and nanoencapsulated oxcarbazepine were comparable across both cell types, likely due to rapid drug release kinetics. Transport studies using fluorescently-labeled nanoparticles (loaded with coumarin-6) demonstrated increased permeability of surfactant-coated nanoparticles. Future developments in enzyme-prodrug therapy and targeted delivery are expected to provide improved options for pregnant patients with epilepsy.